Pengaruh Ukuran Perusahaan, Slack Resource, dan Profitabilitas Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to examine the influence of company size, slack resources, and profitability on corporate social responsibility disclosure, a case study of basic material companies listed on the Indonesia Stock Exchange for the 2021-2024 period. Corporate social responsibility has become a crucial issue in the business world, especially since it was mandated for companies operating in the natural resources sector through Law No. 40 of 2007 concerning Limited Liability Companies. The basic material sector, including mining, chemicals, wood, paper, construction materials, containers, and packaging, plays a vital role in the economy, but faces significant challenges related to the environmental and social impacts of its operational activities. This study employed a quantitative approach and utilized secondary data from annual reports and sustainability reports. Samples were selected using a purposive sampling method, and multiple regression analysis was conducted using SPSS 26 to test the hypotheses. The sample size was 31 companies, spanning a 4-year observation period, resulting in 124 observational data sets. The study shows that company size, slack resources, and profitability simultaneously influence the disclosure of corporate social responsibility. This means that large companies tend to have a greater number and variety of stakeholders, so they will receive greater attention and pressure from stakeholders, so that companies not only implement CSR, but also disclose it. Partially, company size influences the disclosure of corporate social responsibility, while slack resources and profitability proxied using ROA and ROE do not influence the disclosure of corporate social responsibility. This indicates that the size of slack resources and profitability do not influence companies to disclose corporate social responsibility, because companies will still disclose even at a minimal level.